PEMANFAATAN AI GENERATIF DALAM PEMBELAJARAN SASTRA MAKASSAR: INTEGRASI LITERASI LINGUISTIK DAN LITERASI BUDAYA - Sahban Nur; Mahrus Sabang; Puput Kusuma Dewi (Panrita: Jurnal Bahasa dan Sastra Daerah serta Pembelajarannya, 2026)
The development of Generative Artificial Intelligence (GenAI) offers new opportunities for literature learning; however, its application to local literature raises challenges related to linguistic accuracy and cultural representation. This study aims to analyze the potential and limitations of generative AI in Makassar literature learning and to formulate a conceptual framework integrating linguistic and cultural literacy. A structured literature review and conceptual synthesis were conducted using relevant publications from 2023–2026. The findings indicate that generative AI can support text exploration, paraphrasing, translation, and interpretation, but its outputs require linguistic and cultural verification. This study proposes an AI–Linguistic Literacy–Cultural Literacy framework that positions AI as both an interpretive partner and an object of critical evaluation through authentic text reading, AI interaction, verification, interpretation reconstruction, and critical reflection. The framework provides a foundation for critical, ethical, and culturally sensitive AI-assisted Makassar literature learning.